THE ROLE OF RUSTS IN CORROSION AND CORROSION PROTECTION OF IRON AND STEEL - Hussein, Lubna Basem Kazim Abdul; Mater, Anwar Abdalmajeed Abdullah; Clinic, Hanin Khaled Mohammed; Alanbar, Dhuha Mazin Fawzi Khalaf; Ali, Saja Muwafaq Freah (Journal of Medical Genetics and Clinical Biology, 2024)
The processes of atmospheric corrosion of iron and steel and the properties of corrosion products (rusts) are modeled based on a quantitative evaluation of the chemical reactions pertaining to corrosion to elucidate the conditions with which corrosion-protective rust films form. in the initial stage of corrosion, in the rusts, the pH of the aquatic system is maintained at 9.31 owing to an equilibrium with iron (II) hydroxide and the rate of air-oxidation at this pH is very fast, and that dense, self-repairing rust films form, protecting the underlying iron and steel. However, after corrosion stops, the rust film deteriorates due to the dissolution and shrinkage by aging, and the deteriorated rust film separates the anode and cathode reaction products (Fe2+ and OH- ions) to cause crevice corrosion. The air-oxidation of iron (II) in anode channels without the presence of OH- ions results in strongly acidic solutions (pH 1.41), causing acid-corrosion. It is proposed that good catalysts (e.g. copper (II) and phos-phate ions) accelerate the air-oxidation at low pH, delaying the crevice- and acid-corrosion stages. Further, it is argued that iron compounds with negative charges due to the non- stoichiometric proportions of the lattice oxide ions and metal ions (solid oxoanions of iron) exhibit stable cation-selective permeability even with a drop in pH. Rust films including such compounds would stop the passage of aggressive anions and act to protect iron and steel.